FACTORS INFLUENCING ANTIRETROVIRAL MEDICATION ADHERENCE BASED ON THE HEALTH BELIEF MODEL IN HIV/AIDS PATIENTS - Rosita, Eda; Lindayani, Linlin (Jurnal Keperawatan PPNI Jawa Barat, 2023)
Background: Human immunodeficiency virus (HIV) is an infection that leads to the immune system, destroys CD4 cells, and lowers a person's immunity against opportunistic infections. Therefore, antiretroviral (ARV) treatment is needed; ARV itself can slow down HIV. HBM has four dimensions that can describe how individuals believe in a healthy behavior; these dimensions include Perceived Susceptibility, Perceived Severity, Perceived barriers, and Perceived Benefits. Objective: This study aims to determine the factors that influence adherence to taking antiretroviral drugs based on the Health Belief Model. Methods: This research is a quantitative study using a cross-sectional design. Sampling was done by convenience sampling on HIV/AIDS patients who were in KPA Kota Bandung with a total of 184 respondents. Data analysis used person correlation, independent t-test, and one-way ANOVA and used linear regression. Results: The results of the study of factors affecting adherence to taking antiretroviral drugs based on the Health Belief Model using linear regression showed that there was no significant relationship between the total health belief model and adherence, but if divided by domain there was a relationship between HBM domains and adherence. Conclusion: Obtained a value (R2) of 0.124, which means that the effect of side effect variables, CD4 count, Perceived susceptibility, Perceived benefits, and social support on the compliance variable is 12.4% statistically significant with a value (p <0.05).